p75NTR ectodomain is a physiological neuroprotective molecule against amyloid-beta toxicity in the brain of Alzheimer’s disease - Yao, X-Q; Jiao, S-S; Saadipour, K; Zeng, F; Wang, Q-H; Zhu, C; Shen, L-L; Zeng, G-H; Liang, C-R; Wang, J; Liu, Y-H; Hou, H-Y; et al. (Molecular psychiatry, 2015)
In Alzheimer’s disease (AD), neurodegenerative signals such as amyloid-beta (Aβ) and the precursors of neurotrophins, outbalance neurotrophic signals, causing synaptic dysfunction and neurodegeneration. The neurotrophin receptor p75 (p75NTR) is a receptor of Aβ and mediates Aβ-induced neurodegenerative signals. The shedding of its ectodomain from the cell surface is physiologically regulated; however, the function of the diffusible p75NTR ectodomain (p75ECD) after shedding remains largely not known. Here, we show that p75ECD levels in cerebrospinal fluid and in the brains of Alzheimer’s patients and amyloid-beta precursor protein (APP)/PS1 transgenic mice were significantly reduced, due to inhibition of the sheddase-tumor necrosis factor-alpha-converting enzyme by Aβ. Restoration of p75ECD to the normal level by brain delivery of the gene encoding human p75ECD before or after Aβ deposition in the brain of APP/PS1 mice reversed the behavioral deficits and AD-type pathologies, such as Aβ deposit, apoptotic events, neuroinflammation, Tau phosphorylation and loss of dendritic spine, neuronal structures and synaptic proteins. Furthermore, p75ECD can also reduce amyloidogenesis by suppressing β-secretase expression and activities. Our data demonstrate that p75ECD is a physiologically neuroprotective molecule against Aβ toxicity and would be a novel therapeutic target and biomarker for AD.